Drivers of Electric Vehicle Purchase Intention in Indonesia: The Mediating Role of Willingness to Pay - Rafi Ramadhani Risnadi; Citra Kusuma Dewi (ADPEBI Publisher, 2026)
Purpose – This paper seeks to investigate the joint effects of consumer psychology, individual characteristics, and government financial incentives on electric vehicle (EV) purchase intention in Indonesia, utilizing willingness to pay (WTP) as a critical psychological and economic mediator. Methodology/approach – Grounded in the Theory of Planned Behavior (TPB) and Value-Belief-Norm (VBN) theory, an integrated framework featuring seven antecedents was developed. Data were acquired from 392 valid respondents across 33 regions in Indonesia using a purposive sampling method and empirically analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings – The results reveal that resistance to change, environmental concern, perceived value, and personal norms are important direct predictors of purchase intention. Meanwhile, need for uniqueness, perceived trust, and government financial incentives serve as key drivers of readiness to pay. WTP plays a full mediating role in the association between need for uniqueness and purchase intention, while partially mediating the influences of environmental concern, perceived value, and resistance to change. Novelty/value – This study provides a novel theoretical integration of rational-economic and moral-normative pathways to evaluate EV adoption in an emerging market context. The findings challenge the conventional premise that financial subsidies alone drive EV penetration, highlighting instead that internal motivations and customer perceived value serve as more powerful levers for sustainable transport transitions.